Motivation and Vision: An Analysis of Future L2 Self Images, Sensory Styles, and Imagery Capacity Across Two Target Languages - Dörnyei, Zoltán; Chan, Letty (Language learning, 2013)
Recent theorizing on second language (L2) motivation has proposed viewing motivation as a function of the language learners’ vision of their desired future language selves. This would suggest that the intensity of motivation is partly dependent on the learners’ capability to generate mental imagery. In order to test this hypothesis, this study investigates whether learner characteristics are related to sensory and imagery aspects with indices of the strength of the learners’ future L2 self‐guides (ideal and ought‐to L2 selves) and how these variables are linked to learning achievement in two target languages, English and Mandarin, assessed both by self‐report and objective measures. One hundred seventy‐two Year 8 Chinese students (ages 13–15) completed a questionnaire survey, and the results reveal several significant associations between the future self‐guides and intended effort and actual grades, including a consistently positive relationship between the ideal self and the criterion measures. The findings also confirm the multisensory dimension of future self‐guides, suggesting the importance of a broad imagery capacity (including both visual and auditory components) in the development of individuals’ future self‐identities. Finally, the ideal‐self images associated with different languages were shown to form distinct L2‐specific visions, which has various implications for future research with regard to the potential positive or negative interaction of these self images.